Colombian Migration Policy at the Early 20th Century - Gómez, María Angélica (Pontificia Universidad Javeriana, 2014)
This paper studies the first Japanese immigrants in Colombia. 1922-1936). This research is a compilation of legal resolutions dictated in the 1886 Colombia’s Republic Constitution towards immigration. Particularly, this research points out debates around the improvement of the race project through promoting alien immigration in the late 19th and early 20th centuries. To come up with such a compilation, reviewing primary official sources (laws and decrees), discourses and related literature was fundamental. The analysis of the research shows that there is a correlation between diverse laws that allowed or restricted aliens to enter the country. In addition the debates taking place in different groups of the local society around the benefits and disadvantages of letting immigrants enter the country.